Average Error: 0.4 → 0.4
Time: 17.7s
Precision: 64
$\frac{\cos^{-1} x}{\sinh^{-1} \left(\frac{1}{x}\right)}$
$\frac{\cos^{-1} x}{\sinh^{-1} \left(\frac{1}{x}\right)}$
\frac{\cos^{-1} x}{\sinh^{-1} \left(\frac{1}{x}\right)}
\frac{\cos^{-1} x}{\sinh^{-1} \left(\frac{1}{x}\right)}
double f(double x) {
double r1231721 = x;
double r1231722 = acos(r1231721);
double r1231723 = 1.0;
double r1231724 = r1231723 / r1231721;
double r1231725 = asinh(r1231724);
double r1231726 = r1231722 / r1231725;
return r1231726;
}


double f(double x) {
double r1231727 = x;
double r1231728 = acos(r1231727);
double r1231729 = 1.0;
double r1231730 = r1231729 / r1231727;
double r1231731 = asinh(r1231730);
double r1231732 = r1231728 / r1231731;
return r1231732;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.4

$\frac{\cos^{-1} x}{\sinh^{-1} \left(\frac{1}{x}\right)}$
2. Final simplification0.4

$\leadsto \frac{\cos^{-1} x}{\sinh^{-1} \left(\frac{1}{x}\right)}$

# Reproduce

herbie shell --seed 1
(FPCore (x)
:name "acos(x) / asinh(1/x)"
:precision binary64
(/ (acos x) (asinh (/ 1 x))))